Post-Transplantation Cyclophosphamide Uniquely Restrains Alloreactive CD4+ T-Cell Proliferation and Differentiation After Murine MHC-Haploidentical Hematopoietic Cell Transplantation - Hadjis, Ashley D.; Nunes, Natalia S.; Khan, Shanzay M.; Fletcher, Rochelle E.; Pohl, Alessandra de Paula; Venzon, David J.; Eckhaus, Michael A.; Kanakry, Christopher G. (Frontiers in Immunology, 2022)
Post-transplantation cyclophosphamide (PTCy) reduces the incidence and severity of graft-versus-host disease (GVHD), thereby improving the safety and accessibility of allogeneic hematopoietic cell transplantation (HCT). We have shown that PTCy works by inducing functional impairment and suppression of alloreactive T cells. We also have identified that reduced proliferation of alloreactive CD4+ T cells at day +7 and preferential recovery of CD4+CD25+Foxp3+ regulatory T cells (Tregs) at day +21 are potential biomarkers associated with optimal PTCy dosing and timing in our B6C3F1→B6D2F1 MHC-haploidentical murine HCT model. To understand whether the effects of PTCy are unique and also to understand better the biology of GVHD prevention by PTCy, here we tested the relative impact of cyclophosphamide compared with five other optimally dosed chemotherapeutics (methotrexate, bendamustine, paclitaxel, vincristine, and cytarabine) that vary in mechanisms of action and drug resistance. Only cyclophosphamide, methotrexate, and cytarabine were effective in preventing fatal GVHD, but cyclophosphamide was superior in ameliorating both clinical and histopathological GVHD. Flow cytometric analyses of blood and spleens revealed that these three chemotherapeutics were distinct in constraining conventional T-cell numerical recovery and facilitating preferential Treg recovery at day +21. However, cyclophosphamide was unique in consistently reducing proliferation and expression of the activation marker CD25 by alloreactive CD4+Foxp3- conventional T cells at day +7. Furthermore, cyclophosphamide restrained the differentiation of alloreactive CD4+Foxp3- conventional T cells at both days +7 and +21, whereas methotrexate and cytarabine only restrained differentiation at day +7. No chemotherapeutic selectively eliminated alloreactive T cells. These data suggest that constrained alloreactive CD4+Foxp3- conventional T-cell numerical recovery and associated preferential CD4+CD25+Foxp3+ Treg reconstitution at day +21 may be potential biomarkers of effective GVHD prevention. Additionally, these results reveal that PTCy uniquely restrains alloreactive CD4+Foxp3- conventional T-cell proliferation and differentiation, which may explain the superior effects of PTCy in preventing GVHD. Further study is needed to determine whether these findings also hold true in clinical HCT.